2018
DOI: 10.1021/acs.jpcc.8b07015
|View full text |Cite
|
Sign up to set email alerts
|

Halogen-Substituted Acridines as Highly Effective Corrosion Inhibitors for Mild Steel in Acid Medium

Abstract: A series of acridines were designed and synthesized for the development of effective inhibitors for mild steel corrosion in 1 M HCl solution, in which the halogen-substituted acridines showed better inhibitive performance than the nonhalogen-substituted acridines. The corrosion protection properties of the halogen-substituted acridines, including 2-chloro-9-phenylacridine (CPA), 2-chloro-9-(2-fluorophenyl)­acridine (CFPA), and 2-bromo-9-(2-fluorophenyl)­acridine (BFPA), were further investigated using weight l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Such effect can be ascribed to the inhibition of charge transfer due to the strengthened network. 64,65 The phase angle in Bode plots only appears in the low-frequency range and with the increase of immersion time, the trend of increasing phase angle is obvious (Figure 5d), suggesting that the barrier effect of ELSC is gradually enhanced. In addition, the impedance modulus (|Z|0.01Hz), which reflects the ability of a coating to restrain the current between the cathodic and anodic areas, increases significantly (Figure 5d).…”
Section: Spontaneous and Progressive Self-strengtheningmentioning
confidence: 99%
“…Such effect can be ascribed to the inhibition of charge transfer due to the strengthened network. 64,65 The phase angle in Bode plots only appears in the low-frequency range and with the increase of immersion time, the trend of increasing phase angle is obvious (Figure 5d), suggesting that the barrier effect of ELSC is gradually enhanced. In addition, the impedance modulus (|Z|0.01Hz), which reflects the ability of a coating to restrain the current between the cathodic and anodic areas, increases significantly (Figure 5d).…”
Section: Spontaneous and Progressive Self-strengtheningmentioning
confidence: 99%
“…Various acids like hydrochloric acid, sulfuric acid, and phosphoric acid are used for pickling and acidization processes by the pickling industry. These acids used for such pickling processes may cause corrosion and damage to the material used. , …”
Section: Introductionmentioning
confidence: 99%
“…It was found that a semicircular capacitive loop, which is slightly depressed, was displayed in the Nyquist plots. The imperfect capacitive circuit is usually caused by frequency dispersion due to roughness and other inhomogeneities of the electrode surface . Furthermore, the diameter of the capacitive loop with inhibitor was larger than that of the noninhibitor reference, and it increased further with the addition of KI, suggesting a thicker adsorption layer of FYPA + KI than FYPA alone on the steel surface.…”
Section: Resultsmentioning
confidence: 99%
“…The imperfect capacitive circuit is usually caused by frequency dispersion due to roughness and other inhomogeneities of the electrode surface. [21][22][23][24][25] Furthermore, the diameter of the capacitive loop with inhibitor was larger than that of the noninhibitor reference, and it increased further with the addition of KI, suggesting a thicker adsorption layer of FYPA + KI than FYPA alone on the steel surface. It was worth noting that there was no significant change in the shape of impedance at distinct inhibitor concentrations, showing that the addition of the inhibitor did not change the corrosion mechanism of the steel electrode.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%